Деякі стохастичні моделі фінансової математики - Пепеляєва, Т.В. (Теорія оптимальних рішень, 2007)
The some stochastic differential equetions are considered and the desissions of tem are founded. It’s allow to do presicion an interesting rate on the financial market.